Síntese e caracterização de estanatos de cálcio dopados aplicados em processos oxidativos avançados - Vilela, Vanessa Bezerra (2019)
Calcium stannate (CaSnO3) is an orthorhombic perovskite-type semiconductor that presents several technological applications, with a noteworthy use as catalysts in redox processes. In this work, pure CaSnO3 and doped stannate with Fe3+, Cu2+, Co2+ e Pd2+ were synthesized by the modified Pechini method. The catalytic activities of the samples were evaluated by the photo-degradation probe reaction of the textile dye golden yellow remazol. The participation of the reactive species in photo-degradation’s reaction was determined by the use of suppressor agents in order to elucidate the reaction mechanism assumed by each of the photocatalysts. The samples were characterized by thermogravimetric analysis (TG/DTA), X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), infrared spectroscopy (IR), Raman spectroscopy and scanning electron microscopy (SEM). The samples were submitted to terephthalic acid photohydroxylation reaction. The XRD results expressed a change in the long range order of the doped samples caused by the introduction of the doping cations in the crystal lattice. CaSnO3, CaSn0,9Cu0,1O3 e CaSn0,99Pd0,01O3, showed the highest catalytic activity, reaching total degradation of the textile dye. Besides that, these samples showed close band gap values. With the use of suppressors agents in photocatalytic tests, it is able to notice that only CaSn0,9Fe0,1O3 presented the contribution of both charge carriers, photogenerated e- and h+, in the hydroxyl radical generation. While for the other samples, the formation of the hydroxyl radical occurs only by the participation of the photogenerated h+.